2018
DOI: 10.3389/fnana.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Neural Progenitors in the Developing Neocortex of the Northern Tree Shrew (Tupaia belangeri) Show a Closer Relationship to Gyrencephalic Primates Than to Lissencephalic Rodents

Abstract: The neocortex is the most complex part of the mammalian brain and as such it has undergone tremendous expansion during evolution, especially in primates. The majority of neocortical neurons originate from distinct neural stem and progenitor cells (NPCs) located in the ventricular and subventricular zone (SVZ). Previous studies revealed that the SVZ thickness as well as the abundance and distribution of NPCs, especially that of basal radial glia (bRG), differ markedly between the lissencephalic rodent and gyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 93 publications
(173 reference statements)
1
10
0
Order By: Relevance
“…We first concentrated on APs as the primary NPCs. As observed in most mammalian species (Götz et al, 1998;Englund et al, 2005;Osumi et al, 2008;Fietz et al, 2010;Hansen et al, 2010;Reillo et al, 2011;Romer et al, 2018;Sauerland et al, 2018), NPCs of the dwarf rabbit and guinea pig VZ were Pax6+ and largely Tbr2-(Figures 1, 2, 3A,B). The highest abundance of Pax6+ NPCs in the VZ of the dwarf rabbit was observed at day 15 p.c.…”
Section: Developmental Differences In Neurogenesis Between the Dwarf Rabbit And Guinea Pig Neocortexsupporting
confidence: 59%
“…We first concentrated on APs as the primary NPCs. As observed in most mammalian species (Götz et al, 1998;Englund et al, 2005;Osumi et al, 2008;Fietz et al, 2010;Hansen et al, 2010;Reillo et al, 2011;Romer et al, 2018;Sauerland et al, 2018), NPCs of the dwarf rabbit and guinea pig VZ were Pax6+ and largely Tbr2-(Figures 1, 2, 3A,B). The highest abundance of Pax6+ NPCs in the VZ of the dwarf rabbit was observed at day 15 p.c.…”
Section: Developmental Differences In Neurogenesis Between the Dwarf Rabbit And Guinea Pig Neocortexsupporting
confidence: 59%
“…The tree shrew model of AD has been successfully constructed in our study ( 26 ). A recent study has suggested that the neocortex development of the tree shrew is closer to primates than to rodents ( 27 ). This makes the tree shrew a good experimental animal in neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…belangeri chinensis [3]. Previous studies [45] showed that the tree shrew has a closer relationship with humans than did rodents in terms of physiological function, biochemical metabolism and genomic signatures. Due to its unique characteristics, such as small body size, low cost of maintenance, life span and short reproductive cycle, the tree shrew has been increasingly used in laboratory analyses in recent years.…”
Section: Introductionmentioning
confidence: 99%